2020
DOI: 10.1002/cncr.32736
|View full text |Cite
|
Sign up to set email alerts
|

Pain in older survivors of hematologic malignancies after blood or marrow transplantation: A BMTSS report

Abstract: BACKGROUND: Blood or marrow transplantation (BMT) is increasingly offered to older adults with hematologic malignancies; however, their risk for severe pain is poorly understood. Using the Bone Marrow Transplant Survivor Study, the current study investigated the prevalence and predictors of pain after BMT (allogeneic or autologous) as well as its association with physical performance impairments and frailty. METHODS: The cohort included 736 patients with hematologic malignancies who underwent BMT at an age ≥ 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For example, hospitalization rates for pediatric SCD have remained largely unchanged from 2000 to 2016, 46 with pain being the primary reason for hospital admissions 46,47 . Additionally, a subset of patients who receive curative therapies, such as hematopoietic stem cell transplant, continue to experience pain following transplant 48,49 . Although NHLBI and ASH recognize the need for nonpharmacological pain management in SCD, 17–19 there are no standard behavioral treatment guidelines with limited options for behavioral interventions that specifically address SCD‐related pain and associated functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hospitalization rates for pediatric SCD have remained largely unchanged from 2000 to 2016, 46 with pain being the primary reason for hospital admissions 46,47 . Additionally, a subset of patients who receive curative therapies, such as hematopoietic stem cell transplant, continue to experience pain following transplant 48,49 . Although NHLBI and ASH recognize the need for nonpharmacological pain management in SCD, 17–19 there are no standard behavioral treatment guidelines with limited options for behavioral interventions that specifically address SCD‐related pain and associated functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants were identified from the Blood or Marrow Transplant Survivor Study (BMTSS), which is a retrospective cohort study of patients who received HCT at City of Hope (COH), University of Minnesota, or University of Alabama at Birmingham (UAB) for hematologic malignant diseases, or severe aplastic anemia, and survived at least 2 years after HCT [ 3 , 21 , 22 ]. Eligibility requirements for the current trial included: 1) ≥ 18 years of age at the time of study enrollment; 2) ≥ 2 years from HCT and in clinical remission; 3) self-reported as pre-frail or frail on the BMTSS questionnaire using the following criteria: clinically underweight (body mass index < 18.5 kg/m 2 ); exhaustion (self-report of feeling tired); low energy expenditure (self-report of physical activity for < 2 days/week); slowness (self-reported limitations in climbing stairs or walking 1 block); and weakness (self-report of weakness in movement), with the presence of 2 of the indices classified as prefrail and ≥ 3 indices classified as frail [ 3 ]; 4) able to provide written informed consent; 5) physically able and willing to complete all study procedures; 6) English-speaking.…”
Section: Methods and Analysismentioning
confidence: 99%